فاعلية برنامج إرشادي معرفي سلوكي لخفض التشوهات المعرفية وأثره في اجترار الأفكار السلبية لدى أمهات الأطفال ذوي الإعاقة الفكرية - محمد، محمد مصطفى طه; خليفة، أسماء محمد علي (جامعة بني سويف - كلية التربية, 2022)
يهدف هذا البحث إلى التحقق من مدى فاعلية برنامج إرشادي معرفي سلوكي لخفض التشوهات المعرفية لدى أمهات الأطفال ذوي الإعاقة الفكرية وأثر هذا البرنامج في اجترار الأفكار السلبية لديهم. وتم استخدام المنهج التجريبي ذي المجموعتين، وبلغ الحجم الكلى للعينة (40) أما من أمهات الأطفال ذوي الإعاقة بمدرسة الفكرية بمحافظة بني سويف ممن تراوحت أعمارهم ما بين (٢٥-٣٥) عاما، بمتوسط عمري (30.5) عاما، وانحراف معياري قدره (7.5) تم تقسيمهم إلى مجموعتين: تجريبية، وضابطة، كل منهم ٢٠ أما، وتم استخدام مقياس التشوهات المعرفية؛ إعداد/ الباحثان، مقياس اجترار الأفكار السلبية إعداد الباحثان، والبرنامج الإرشادي المعرفي السلوكي إعداد/ الباحثان، وقد أسفرت نتائج البحث عن وجود فروق ذات دلالة إحصائية بين متوسطات درجات أفراد المجموعتين: التجريبية، والضابطة، في التطبيق البعدي على مقياس التشوهات المعرفية لصالح المجموعة التجريبية تعزى للبرنامج الإرشادي، عدم وجود فروق ذات دلالة إحصائية بين متوسطات درجات المجموعة التجريبية في القياسين البعدي والتتبعي على مقياس التشوهات المعرفية، ووجود فروق ذات دلالة إحصائية بين متوسطات درجات المجموعتين التجريبية والضابطة في التطبيق البعدي على مقياس اجترار الأفكار السلبية لصالح المجموعة التجريبية، عدم وجود فروق ذات دلالة إحصائية بين متوسطات درجات المجموعة التجريبية في القياسين البعدي والتتبعي على مقياس اجترار الأفكار السلبية. The aim of this research is to verify the effectiveness of a cognitive behavioral program in reducing cognitive distortions among mothers of children with disabilities and the effect of this program on ruminating negative thoughts, and the total sample size was 40 As for the mothers of children with disabilities at Al Fikriah School in Beni Suef Governorate, whose ages ranged between (25-35) years, My mean age (30.5) is general, and defense standard deviation is (7.5) they were divided into two experimental and control groups, each of whom was 20 mothers. The scale of cognitive distortions prepared by the two researchers was used, the scale of rumination of negative thoughts prepared by the researchers, and the cognitive-behavioral program prepared by the two researchers, and the experimental approach with two groups was used, The results of the research resulted in the presence of statistically significant differences between the mean scores of the experimental and control groups in the post application on the cognitive distortions scale in favor of the experimental group due to the counseling program. Statistically significant between the mean scores of the experimental and control groups in the post application on the scale of rumination of negative thoughts in favor of the experimental group, there are no statistically significant differences between the mean scores of the experimental group in the post and follow-up measurements on the scale of rumination of negative thoughts.
Keywords: التربية الخاصة -- ذوي الهمم -- الأفكار السلبية -- الإرشاد المعرفي السلوكي